Marine Phytoplankton Composition in Southern Coast of Sarawak - Teng, Sing Tung; Afiqah, Hamilton Hanifah; Othman, Bojo; Law, Ing Kuo (UNIMAS Publisher, 2024)
Southern coast of Sarawak is one of the Biodiversity hotspot in tropical zone. However, this area is affected by the coastal development and tourism activities in recent years. Phytoplankton is a group of microorganism which plays an important role in primary production and is baseline in food web. The composition is important to determine the quality and safety of the aquatic resources. In this study, we aim to study the phytoplankton composition at southern coast of Sarawak, including Sematan, Samunsam, Teluk Melano and Tanjung Datu. A total of eight phytoplankton samples were collected at nine selected stations during the Tanjung Datu-Samumsam expedition in August, 2018. A total of 31 taxa were recorded including 21 taxa belong to diatom and 9 taxa belong to dinoflagellate in this study. The phytoplankton density was ranged from 604 cell L-1 to 2190 cell L-1. The station S1 showed highest cell density compare to other station The predominant genera were Chaetoceros, Guinardia, Leptocylindrus, Nitzschia, Pleurosigma and Rhizosolenia. The station S8 showed highest diversity with recorded 23 taxa. The station S7 showed lowest diversity with 13 taxa. The clustering analysis was showed four type of the phytoplankton communities found in this study. Seven genera were potential harmful algal species. The finding in this study was served as baseline data reference for future phytoplankton monitoring work.